Advances in recovery and utilization of carbon dioxide: A brief review. Issue 4 (August 2021) - Godin, Jessica; Liu, Weizao; Ren, Shan; Xu, Chunbao Charles
Abstract: The continued warming of the planet resulting from anthropogenic CO2 emissions requires immediate action to meet climate change mitigation targets. The utilization of CO2 from waste streams and ambient air has attracted increasing attention as a powerful emission mitigation tool. This review aimed at exploring the current state of carbon capture and utilization technologies. Various separation techniques, including absorption, adsorption, membrane, cryogenics, and chemical looping were explored in this review, with their challenges and future prospects identified. Utilization of CO2 via conversion to fuels and chemicals, as a green solvent and enhanced oil recovery, as well as through mineral carbonation were explored. Conversion of CO2 to synthetic fuels appears to be the very promising pathway to scaling up carbon capture technologies due to the value of the products. The costs and sustainability aspects of capture and utilization technologies, as well as the challenges and future prospects for CO2 utilization were discussed. Graphical Abstract: ga1 Highlights: This review focuses on a selection of technologies and methodologies used to convert CO2 into useful products. Sources of CO2 emissions and the possible capturing methods were outlined. Technological challenges for CO2 capture and utilization methods were identified. The economic feasibility of CO2 capture was examined for various utilization routes.